A magnetic‐loop based monopole antenna for GPR applications. Issue 4 (28th December 2018) - Raza, Ali; Lin, Wenbin; Liu, Yunlin; Sharif, Abu Bakar; Chen, Yanzheng; Ma, Cunliang
Abstract: A new planar antenna is proposed for multiple applications in ground‐penetrating radar. The proposed antenna offers ultra‐wide band characteristics ranging from 100 MHz to 6 GHz. The antenna composed of two elements: an electrical tree‐shaped portion and a magnetic loop antenna, made by joining an electrical antenna with a ground plane via 50 Ohm resistor. The loop antenna portion provides a low‐frequency operation without increasing physical size of the antenna. Proposed antenna has relatively small dimensions 20 × 22.5 cm 2 as compared with similar antennas covering the same bandwidth. Time domain analysis of this antenna is done to check its performance for applications in impulse‐based radar systems. The antenna has been manufactured and experimental results are added to validate simulation results.